PERAN KH AHMAD ZAMACHSYARI DALAM MENGEMBANGKAN PENDIDIKAN ISLAM DI PONDOK MODERN AL- RIFA’IE GONDANGLEGI MALANG - Rani Rahim; Moh. Muslim; Indhra Mushtofa (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Pondok pesantren is oldest institution of education that continues to grow and develop along with the development of the educational world. Therefore, in this study researchers tried to find in Pondok Modern Al-Rifa'ie Gondanglegi with formula problem: 1) how education education education education education Islam KH. Achmad Zamachsyari 2) how to Implement Educational Development KH. Achmad Zamachsyari at Pondok Modern Al-Rifa'ie Malang, 3) how KH. Achmad Zamachsyari was the development of Islamic education in Pondok Modern Al-Rifa'ie Malang. Data analysis by reducing irrelevant data, presenting data and drawing conclusions. 1) Islamic education thought. Achmad Zamachsyari is Making a change by building modern boarding school in Malang in terms of his book teaching He wants this cottage to be given a public school and foreign language skills. 2) Implementation of educational development KH. Achmad Zamachsyari namely For the formal school curriculum in Al-Rifa'ie to be adapted by the current government using the KTSP and plans also follow the 2013 curriculum, For the curriculum the orientation remains in the religious sciences, such as tauhid, akhlak, Nahwu-shorof, fiqh, tafsir, and Balaghoh and For the Al-Qur'an Curriculum there is a tahfidzul Al-Qur'an musabaqoh suroqotul oshri program. There is also the cultivation of foreign language intelligence capabilities and the denial of life skills. 3) Results KH. Achmad Zamachsyari in the development of Islamic education in Pondok Modern Al-Rifa'ie.